Quality Status and Skin-Related Functional Properties of Traditional Korean Fermented Vinegars - Hwan Hee Yu; So-Won Jang; Eungyeong Kim; Jong-Chan Kim; Mi Jang (Foods)
The correlation between fermented vinegar’s physicochemical properties and functional characteristics, particularly skin-related functionalities, remains unclear. We analyzed the quality of widely consumed Korean fermented vinegars, including grain and persimmon vinegars, and their correlation with skin-related functionalities to establish quality control criteria linked to functional properties. Fifteen traditional Korean grain vinegars and fourteen persimmon vinegars were collected; distilled white vinegar was used as the control group. Grain vinegars showed 3.57–100.00% collagenase and 62.38–77.03% tyrosinase inhibition; persimmon vinegars showed 0.00–94.50% and 30.75–71.54%, respectively. To determine which quality characteristics are high in fermented vinegar with high skin-related functionality, a correlation analysis was conducted. In grain vinegar, total nitrogen and free amino acids were strongly associated with skin-related functionalities. In persimmon vinegar, organic acids, particularly lactic acid, were correlated with skin-related effects; thus, both demonstrated the importance of quality assessment. Insights into relationships between the composition and functional properties of fermented vinegar were gained. Specific quality markers for managing skin-related functionality of Korean fermented vinegar established a scientific basis for standardizing quality control, developing high-value functional vinegar products, and ensuring consistent product quality.